Vocational and technical education in Turkey: Problems and recommendations - Varol, Asaf (Publ by IEEE, 1991)
It is noted that within the last few years many two-year vocational schools of higher education have been established in Turkey. But there are not enough lecturers to teach technology in these colleges. In addition, ample tools and study materials have not been supplied until recently. The author discusses the role played by engineers in technical education, the undergraduate and graduate curricula of the technical education facilities, the employment fields of graduates from technical education facilities, and the student selection for technical education programs. Finally, some important recommendations that are based on research at the Technical Education School of Firat University are given.
21st Frontiers in Education Conference -- 21 September 1991 through 24 September 1991 -- West Lafayette, IN, USA -- 16954
Keywords: Technical Education Programs; Turkey Technical Education; Turkey Vocational Education; Engineering Education